2014
DOI: 10.1016/j.appet.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on dietary variety - Results from a twin study

Abstract: A B S T R A C TThe heritability of variety seeking in the food domain was estimated from a large sample (N = 5,543) of middle age to elderly monozygotic and dizygotic twins from the "Virginia 30,000" twin study. Different dietary variety scores were calculated based on a semi-quantitative food choice questionnaire that assessed consumption frequencies and quantities for a list of 99 common foods. Results indicate that up to 30% of the observed variance in dietary variety was explained through heritable influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In particular, it is assumed that disgust prevents an organism from coming in contact with hard‐to‐detect parasites and is therefore sensitive to cues that indicate a risk for pathogenic contamination (Curtis, de Barra, & Aunger, ). In our ancestral past, every unknown food source entailed the risk of eating harmful substances (Clifford & Wendell, ; Nesse, ; Prokop et al., ; Scheibehenne et al., ). Given the burden of low food availability, our ancestors were pressed to find new food sources and eat anything available.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is assumed that disgust prevents an organism from coming in contact with hard‐to‐detect parasites and is therefore sensitive to cues that indicate a risk for pathogenic contamination (Curtis, de Barra, & Aunger, ). In our ancestral past, every unknown food source entailed the risk of eating harmful substances (Clifford & Wendell, ; Nesse, ; Prokop et al., ; Scheibehenne et al., ). Given the burden of low food availability, our ancestors were pressed to find new food sources and eat anything available.…”
Section: Introductionmentioning
confidence: 99%
“…Our results lend increasing support to a growing number of studies that have highlighted the importance of genetic factors across several consumption domains. For example, in a study using middle aged through elderly adults twins, 30% of the variation in individuals' search for variety of food was explained by additive genetic factors (Scheibehenne et al, 2014). Other studies have shown moderate heritable influences in the use of various heuristics and biases ranging from small to large heritable contributions, though estimates differ depending on the size of samples, ages, and nationality of twins (Cesarini et al, 2012;Simonson & Sela, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Previous twin studies have shown that a strong genetic component defines consumption of some specific foods such as coffee and garlic (Teucher et al, 2007), beverages including soda and alcohol (de Castro, 1993), energy and macronutrient intake (Faith et al, 1999;Hasselbalch et al, 2008;Liu et al, 2013), healthy/unhealthy pattern as well as food liking/disliking (Pallister et al, 2015;Vink et al, 2020), eating behavior (Tholin et al, 2005) and variety in the overall diet (Scheibehenne et al, 2014). However, the full extent of the genetic impact on dietary indices has never been fully explored.…”
mentioning
confidence: 99%